Optimization of quick tool changeovers: the SMED methodology in a dental products industry - Souza, Henrique Granado de; Guedes, Karoline (Brazilian Journal of Production Engineering, 2025)
In the face of the challenges of the globalized market, the optimization of production processes becomes crucial. Developed by Shigeo Shingo, SMED stands out in reducing setup time in industrial machines. This research focuses on operational efficiency, especially in reducing setup time, identifying it as a critical point for the dental products company. The study involved collecting data on the setup process, highlighting disassembly, cleaning and assembly of the machine. SMED adopted the separation of activities, elimination of non-essentials and standardization. Proposals included anticipating cleaning and involving two operators. Standardization occurred through Standard Operating Procedures (SOPs) and visual management. Training ensured understanding and adherence. Results showed a significant reduction of more than three hours in setup time, generating savings in production hours and increased efficiency. The study highlights the importance of SMED in improving industrial processes, highlighting benefits such as cost reduction, increased production capacity and flexibility. The successful implementation demonstrated tangible gains in efficiency and productivity.
Keywords: smed; quick tool change; dental industry